2014
DOI: 10.1002/2013ja019624
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Electron demagnetization and heating in quasi‐perpendicular shocks” by Mozer and Sundkvist

Abstract: In their paper, Mozer and Sundkvist (2013) present important observations of large-amplitude high-frequency electric field fluctuations in the vicinity of the ramp region of the Earth's bow shock. In common with other recent work, they emphasize the role of electron scattering by such fluctuations in the problem of electron heating at collisionless shocks, relegating the DC fields to providing a reservoir of energy which can be tapped apparently to whatever degree is required. While the historical approach of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…On the contrary, analysis of a particular Earth bow shock crossing by Cluster showed that the electron heating is rather isotropic and operates 10.1029/2018GL077835 predominantly within the ramp (Schwartz et al, 2011). This indicates that some mechanism of electron isotropization (pitch-angle scattering) should operate within supercritical shocks (but see also discussion by Schwartz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, analysis of a particular Earth bow shock crossing by Cluster showed that the electron heating is rather isotropic and operates 10.1029/2018GL077835 predominantly within the ramp (Schwartz et al, 2011). This indicates that some mechanism of electron isotropization (pitch-angle scattering) should operate within supercritical shocks (but see also discussion by Schwartz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The key controversy concerning electron heating lies in how and when irreversible dissipation occurs. A widely accepted picture of electron heating at the Earth's bow shock describes that the electron phase space is inflated by a quasi-static cross-shock potential accelerating (decelerating) incoming (escaping) electrons, conserving the first adiabatic invariant, and creates an inaccessible region at energies lower than the cross-shock potential energy of electrons [6][7][8][9][10][11][12]. The inaccessible region is postulated to be filled by wave-particle scattering, leading to thermalization and thus irreversibility [e.g., 8,[12][13].…”
mentioning
confidence: 99%
“…A widely accepted picture of electron heating at the Earth's bow shock describes that the electron phase space is inflated by a quasi-static cross-shock potential accelerating (decelerating) incoming (escaping) electrons, conserving the first adiabatic invariant, and creates an inaccessible region at energies lower than the cross-shock potential energy of electrons [6][7][8][9][10][11][12]. The inaccessible region is postulated to be filled by wave-particle scattering, leading to thermalization and thus irreversibility [e.g., 8,[12][13]. The picture is based on past observations of heated "flat-topped" distributions [6,[13][14] and approximately isotropic temperature increase through the shock ramp [e.g., 7,8,13].…”
mentioning
confidence: 99%
“…For instance, it could result from core electrons being energized to suprathermal energies, initially starting with a larger equivalent kappa value, thus increasing the overall suprathermal exponent value. The increase in κ eh could also result from acceleration through a quasi-static electric field (e.g., Schwartz et al 1988Schwartz et al , 2011Schwartz 2014;Scudder et al 1986) for a one-dimensional VDF. The change in κ eh for a two-dimensional VDF in velocity space is complicated if the quasi-static electric field is not uniformly aligned with both component directions in velocity space, as a kappa VDF is not a simple powerlaw (e.g., Livadiotis 2015).…”
Section: Exponentsmentioning
confidence: 99%